Experimental investigation on the thermal performance of heat recovery system with gravity assisted heat pipe charged with R134a and R410A - YILMAZ, MUSTAFA (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The purpose of this study is to investigate the thermal performance of heat recovery system with gravity assisted heat pipe charged R134a and R410A working fluids and also determine the usefulness of heat pipe bundle system in heat recovery applications. For this purpose an experimental test rig was designed and built. Series of experimental tests were carried out by varying the flue gas temperature (75, 100, 125, 150 and 175 degrees C), flue gas velocity (1, 1.5, 2 and 2.5 m/s) and cooling water flow rates (1, 2, 3 and 4 l/min). Values of the overall effectiveness of the heat pipe heat recovery system are shown to vary with the flue gas velocity, as expected, but the results also allow the prediction of effectiveness variation with the variation of the flue gas temperature. Effectiveness of the heat pipe for both working fluids R134a and R410A has been varied averagely between 35.6% and 57.7% with a good agreement with the published results. Quantitatively, it is found that R134a working fluid is 14% more effective than R410A in heat pipe bundle system. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Heat recovery; Heat pipe; R134a and R410A refrigerants; EXCHANGER HPHE; THERMOSIPHON; STORAGE; REFRIGERANTS